2021
DOI: 10.1038/s41598-021-94276-4
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory model test study of the hydrological effect on granite residual soil slopes considering different vegetation types

Abstract: The problems caused by the interaction between slopes and hydrologic environment in traffic civil engineering are very serious in the granite residual soil area of China, especially in Guangdong Province. Against the background of two heavy rainfall events occurring during a short period due to a typhoon making landfall twice or even two typhoons consecutively making landfall, laboratory model tests were carried out on the hydrological effects of the granite residual soil slope considering three vegetation typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Plant canopies reduce the surface runoff by intercepting rainfall and reduce splash erosion caused by rainfall (Mendes et al, 2021). Plant roots improve soil stability and infiltration capacity (Chen et al, 2021). Litter increases the surface roughness, absorbs moisture, reduces raindrop splash erosion, and reduces the runoff velocity (Du et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant canopies reduce the surface runoff by intercepting rainfall and reduce splash erosion caused by rainfall (Mendes et al, 2021). Plant roots improve soil stability and infiltration capacity (Chen et al, 2021). Litter increases the surface roughness, absorbs moisture, reduces raindrop splash erosion, and reduces the runoff velocity (Du et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Litter increases the surface roughness, absorbs moisture, reduces raindrop splash erosion, and reduces the runoff velocity (Du et al, 2019). Plant stems and leaves can intercept the sediment, thereby reducing the amount of eroded sediment (Chen et al, 2021). Liang et al (2020) revealed that sediment reduction was more significant than runoff reduction when the slope was covered with vegetation.…”
Section: Effects Of Different Vegetation Patterns On Runoff and Sedim...mentioning
confidence: 99%
“…Laboratory tests have also been conducted to study the effects of vegetation on the hydrology of slope stability. For example, Chen et al (2021) and Qin et al (2022) discussed how the vegetation type can induce different hydrological effects on the permeability and water storage capacity of slope soil, improving the erosion resistance and so playing a suitable and not negligible role in slope stability response. Yildiz et al (2019), based on the results of experiments on root-permeated specimens in an inclinable large-scale direct shear apparatus, studied the contribution of plant-induced suction to shear strength for root-permeated soils, planted with combinations of different species.…”
Section: Understanding Landslide Hydrological Processes Through Exper...mentioning
confidence: 99%
“…An important issue in infrastructure construction is slope stability [ 1 , 2 , 3 ], which involves ecological restoration, economy and landscaping, and slope protection with vegetation technology [ 4 , 5 , 6 ], usually building green slopes by planting trees and grass between soil beams and frames. Slope micrometeorology determines the growth trend of the protection vegetation, which affects the stability of the slope [ 7 ].…”
Section: Introductionmentioning
confidence: 99%